Microwave-assisted synthesis of Nb2O5 for photocatalytic application of nanopowders and thin films. Issue 17 (27th March 2017) - Falk, Gilberto; Borlaf, Mario; López-Muñoz, María José; Fariñas, Juan Carlos; Rodrigues Neto, João Batista; Moreno, Rodrigo
Abstract: Abstract : A new rapid and energy saving method for the obtention of high performance nanoparticles and thin films of Nb2 O5 by microwave-assisted hydrothermal synthesis is reported. The hydrothermal treatment of a sol–gel precursor solution in a microwave oven at 180 °C for 20 min was enough to obtain amorphous nanoparticles with average sizes of 40 nm. The calcination promotes the formation of different phases of Nb2 O5 (TT and T) with pseudohexagonal and orthorhombic structure, respectively, that transform at higher temperatures in a mixture of orthorhombic and monoclinic phases. Crystalline phase composition was found to have a significant influence on the photocatalytic activity. The best photocatalytic performance was observed for the material mainly constituted by the TT-Nb2 O5 phase. Thin films constituted by the TT phase were prepared by dip-coating. Photocatalytic experiments confirmed the high photocatalytic activity of this material, which showed a kinetic curve similar to that of a reference TiO2 -P25 thin film.